Employing Online Paraphrasing Tools to Overcome Students’ Difficulties in Paraphrasing - Nurul Inayah A. M; Siti Drivoka Sulistyaningrum (Stairs, 2021)
This study aimed to investigate the mechanical engineering vocational education students’ difficulties in making paraphrasing in academic writing course and to investigate the use of the online paraphrasing tools in overcoming those difficulties. The data were taken from two questionnaires distributed to the students regarding the two problems mentioned previously. The items were adapted from Paraphrasing Strategy theory by Schuemann (2006), and Kirszner (2008) which consists of four strategies: 1) changing its synonym; 2) changing part of speech; 3) changing the sentence pattern from active to passive; 4) keep using keywords from the original text. The study revealed that the most commonly used strategy was to change the synonyms with a percentage of 69%. Then, the most difficult problems in terms of content, structure, language, and paraphrase strategy are paraphrasing itself, using punctuation, identifying the part of speech, and inability to state the same information as the source text. Further research is needed in which a more significant number of participants and various academic writing difficulties should take part in, and a variety of research instruments should be employed.